Progress, risks and impacts of the evolution of autonomous vehicles - Hossain, Md Naeem; Rahman, Md Mustafizur; D., Ramasamy; K., Kadirgama; Noor, M. M. (Semarak Ilmu Publishing, 2026)
In recent years, there has been a growing interest in autonomous driving due to the potential to alleviate the responsibilities of drivers and enhance driving safety. A lot of technological advancements and progress have been observed to develop and facilitate the operation of autonomous vehicles. However, the rapid evolution of autonomous vehicles presents a complex and multifaceted set of challenges and opportunities that require in-depth analysis. This review article critically examines the progress made in the development of autonomous vehicle technology, delineates the associated risks, and investigates the multifaceted impacts on society, the economy, and the environment. The article commences by outlining the achievements made in autonomous vehicle technology, incorporating developments in sensor technology, artificial intelligence, and vehicle-to-everything communication for its regular operation, object detection, and prediction mechanism. Additionally, it explores the various levels of automation, from driver assistance systems to fully autonomous vehicles, and the technical challenges encountered at each stage. Moreover, it discusses concerns related to safety, cybersecurity, ethical considerations, and the potential displacement of traditional transportation jobs which need to be overcome by continuous research in this field. In addition to the technological and safety aspects, this review explores the broader societal and environmental impacts of autonomous vehicles. Furthermore, it examines the potential benefits, such as reduced traffic congestion, improved road safety, and enhanced accessibility for individuals with mobility challenges. Conversely, it also considers the environmental consequences and the need for sustainable autonomous mobility solutions.